The Crisis in the Humanities : Transdisciplinary Solutions. - Cvejic, arko (Cambridge Scholars Publishing, 2016)
This volume will appeal to the reader interested in the so-called "long crisis in the humanities" and transdisciplinary approaches as a possible way out of this. It comprises a selection of 23 essays by both established and young scholars from the United States, Slovenia, Croatia, and Serbia, coming from a variety of disciplines, including aesthetics, anthropology, architecture, art, critical theory, ethnography, feminism, film studies, gender and queer theory, literary theory, Marxism, musicology, philosophy, and sociology, among others. What brings all these together here is the intention to